Imran Khan protests (Pakistan) - Voidly (Voidly Global Censorship Index, 2022)
CRITICAL severity censorship detected in Pakistan. Data sourced from OONI.
Censorship Incident ID: PK-2022-0001. Severity: critical. Confidence: 90%